EFEKTIVITAS TEKNIK SOSIODRAMA UNTUK MENINGKATKAN KOMUNIKASI INTERPERSONAL SISWA - Zuhara, Evi (2014)
Masaremajamerupakanmasasosialkarenasepanjangmasaremajahubungansosialsemakintampakjelasdansangatdominan.Hubungansosialakanterjalindenganbaikapabilaterdapatkomunikasi interpersonal di dalamnya. Siswa yang memiliki kesulitan melakukan komunikasi interpersonal akan sulit menyesuaikan diri, cenderung memaksakan kehendak dan egois, Penelitianbertujuanmengetahui efektivitas teknik sosiodrama untukmeningkatkankomunikasiinterpersonal siswa serta menghasilkanrumusan intervensi yang efektifuntuk meningkatkankomunikasi interpersonal siswa. Masalahutamapenelitianadalah"Apakahteknik sosiodrama efektifuntukmeningkatkankomunikasiinterpersonal siswakelas X Kartika Siliwangi 2 Bandung".Metodepenelitian yang digunakanyaitukuasieksperimendenganEquivalent Pretest-Posttest Control Group Design.Sampelpenelitian15siswa, 8 siswa kelompok eksperimen dan 7 siswa kelompok kontrol.Hasil penelitian menunjukkan teknik sosiodrama efektifuntukmeningkatkankomunikasiinterpersonal ditandai pada perubahan kemampuan komunikasi interpersonal siswa pada setiap aspeknya serta peningkatan yang signifikanskor rata-rata saatpretestdan posttest. Rekomendasipenelitianditujukankepada (1) guru bimbingan dan konseling, dapat mempergunakan rumusan intervensi teknik sosiodramasebagai pedoman melakukan layanan bimbingan dan konseling untukmeningkatkankomunikasiinterpersonal siswadan (2) penelitiselanjutnya, dapatmenggunakanpengungkapkomunikasi interpersonal dilihatdarifakto-faktor yang mempengaruhihubungan interpersonal, diantaranya persepsi interpersonal dan konsep diri. Adolescence is a period of social because all of social relationships is becoming more obvious and very dominant. Social relationship will be established with good interpersonal communication when there is in it. Students who have difficulty in interpersonal communication will be difficult to adjust themselves, tend to be overbearing and selfish. The aims of this research is to determinethe effectiveness ofthe sociodrama techniquetoimproveinterpersonalcommunicationstudents,andresulted in the formulationof effectiveinterventionstoimprovestudents'interpersonalcommunication. The main of research problem was "Is sociodrama technique will be effectived for enhancing students' interpersonal communication grade X students of Kartika Siliwangi 2 Senior High School in Bandung". The research methodused is quasi-experimental with Equivalent Pretest-Posttest Control Group Design. The research sampleof 15 students, 8 students in experiment group and 7 students in control group. The results showedthat thesociodrama techniqueis effectiveto improve interpersonal communicationmarked at thechangestudents'interpersonalcommunication skillsinevery aspectanda significantincrease inthe averagescoreswhenpretestandposttest. The research recommendations addressed to (1) guidance and counseling teacher, canuse theformulaof sociodrama technique as a guideline to perform guidance and counseling services to improve students' interpersonal communication and (2) The researcherscan then use therevealerof theinterpersonalcommunicationseenfromthe factorsthataffectinterpersonalrelationships,which areinterpersonal perceptionandself-concept.